2016
DOI: 10.1371/journal.pone.0162895
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Pharmacological Profile and Docking Studies of New Sulfonamides Designed as Phosphodiesterase-4 Inhibitors

Abstract: Prior investigations showed that increased levels of cyclic AMP down-regulate lung inflammatory changes, stimulating the interest in phosphodiesterase (PDE)4 as therapeutic target. Here, we described the synthesis, pharmacological profile and docking properties of a novel sulfonamide series (5 and 6a-k) designed as PDE4 inhibitors. Compounds were screened for their selectivity against the four isoforms of human PDE4 using an IMAP fluorescence polarized protocol. The effect on allergen- or LPS-induced lung infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…To evaluate whether these tadalafil derivatives retained PDE5 inhibition, an IMAP-FP (immobilized metal ion affinity-based fluorescence polarization) assay , was conducted using tadalafil as a reference. Compounds ( 1p , q , 1v , w , 2b – e , 2i – k , 2m , n , and 2q ) with good AChE inhibition (IC 50 < 1 μM) were selected to determine the PDE5 inhibitory activity to identify good dual-target AChE/PDE5 inhibitors, and the results are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate whether these tadalafil derivatives retained PDE5 inhibition, an IMAP-FP (immobilized metal ion affinity-based fluorescence polarization) assay , was conducted using tadalafil as a reference. Compounds ( 1p , q , 1v , w , 2b – e , 2i – k , 2m , n , and 2q ) with good AChE inhibition (IC 50 < 1 μM) were selected to determine the PDE5 inhibitory activity to identify good dual-target AChE/PDE5 inhibitors, and the results are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Following, an IMAP-FP (immobilized metal ion affinity-based fluorescence polarization) assay , was conducted to evaluate the PDE5 inhibitory activities of these tadalafil derivatives with good AChE inhibition (IC 50 < 1 μM), using tadalafil as a reference, and the results are shown in Table . These data showed that most of the tested compounds could retain PDE5 inhibition, with IC 50 values of 0.050–3.231 μM.…”
Section: Resultsmentioning
confidence: 99%
“…Barbosa and colleagues [46] described a series of combretastatin A-4 analogs based on the N-acylhydrazone (NAH) LASSBio-1586 (54) with cytotoxic and antimitotic activity (Figure 14). Homologation [9] studies on the amide nitrogen led to the benzyl homolog of LASSBio-1586 (54), LASSBio-2070 (56), which showed microtubule-stabilizing behavior, while the methylated homolog, LASSBio-1735 (55), had microtubule-destabilizing behavior.…”
Section: Putative Dual Inhibitor Of Tubulin and Egfr By Phenotypic Ap...mentioning
confidence: 99%